Amberlite ir 120 cation excharger mixed matrix membrane for iron removal - Ganeshmorthy, Sekaran (2014)
Heavy metals have been excessively released into the environment due to rapid industrialization and have created a major global concern. Iron is one of the heavy metal pollutant involves in mining activities, foundries and smelters, steel producing industries, and diffuse sources such as piping, combustion by products, constituents of products and many more. There are many methods have been proposed for the removal of iron ions from wastewater such as chemical precipitation, electrochemical reduction, ion exchange, adsorption, biosorption, membrane filtration, coagulation and flocculation. In the current study, ion exchanger mixed matrix membrane (MMM) was used to adsorb iron from aqueous solution. Several potential cations exchanger resins were screened for the maximum iron removal which are Amberlite JR 120, Amberlyst, Lewatit Monoplus TP 214 and Lewatit CNP 105. The selected resin, Amberlite JR 120 was embedded into the mixture of 15 wt.% and 20 wt.% ethylene vinyl alcohol in dimethylsulfoxide and 1- octanol solution. Conventional casting method was used to prepare the flat sheet MMM. The effect of iron concentration from 50ppm to 500ppm was studied in batch adsorption experiment. At initial iron concentration of 500 ppm, 15% and 20% polymer EVAL loading in MMM showed 298.6 and 196.1 mg Fe/g MMM binding capacity respectively. The MMM can be regenerated using 10% HC1 solution which gives about 86% of iron recovery.